Academic Senate Minutes 2005-04-14 - Academic Senate:::::::::
Chair's Report. Agenda approved. Minutes of 3/24/05 approved. Update on WASC. Resolution in Support of SRJC faculty approved. Program review protocol tabled to next meeting. Grade Appeal Policy Revision First Reading. Honors Graduation Policy First Reading. Administrative Credential from Education approved. Statewide Senator report. Academic Freedom statement First Reading. Report from Senator Goodman regarding Resolution Boycotting McGraw-Hill. Questions for the President. Reports from Associated Students, Chair-Elect, EPC, FSAC, SAC and Secretary to the Senate.